Ovine gastrointestinal parasite burden and the impact of strategic anthelmintic treatment strategy in community-based breeding sites in Ethiopia - Molla, W.; Moliso, Mesfin M.; Gizaw, Solomon; Nane, T.; Arke, A.; Ayele, F.; Knight-Jones, Theodore J.D. (Frontiers Media, 2023)
Introduction: In Ethiopia, small ruminants contribute significantly to livelihoods and food security but productivity is low with high disease burden and essential endoparasite control not widely practiced. The current study assessed worm burden and its control in three districts in Ethiopia.